Nonlinear Random Vibration of Functionally Graded Plates - Dogan, Vedat (ASMEDC, 2010)
The nonlinear random vibration of functionally graded plates under random excitation is presented. Material properties are assumed to be independent of temperature. The plates are assumed to have isotropic, two-constituent material distribution through the thickness. The modulus of elasticity, thermal expansion coefficient and density vary according to a power-law distribution in terms of the volume fractions of the constituents. The Classical Plate Theory (CPT) is employed for analytical formulations. Geometric nonlinearity due to in-plane stretching and von Karman type is considered. A Monte Carlo simulation of stationary random processes, multi-mode Galerkin-like approach, and numerical integration procedures are used to develop linear and nonlinear response solutions of clamped functionally graded plates. Uniform temperature distributions through the plate are assumed. Numerical results include time domain response histories, root mean square (RMS) values and response spectral densities. Effects of material composition and temperature rise are also investigated.